alguém me ajuda por favor...Obrigado
Anexos:
![](https://pt-static.z-dn.net/files/d53/0d95eca8a874f3b9634c94df93f23621.jpg)
Soluções para a tarefa
Respondido por
1
f(π) = 2π + 7
f(√2) = 2√2 + 7
[(2π + 7) - (2√2+7)] / (π - √2) =
= [2π + 7 - 2√2 - 7)] / (π - √2) =
= [2π - 2√2] / (π - √2) =
= 2((π - √2)) / (π - √2) =
=2
f(√2) = 2√2 + 7
[(2π + 7) - (2√2+7)] / (π - √2) =
= [2π + 7 - 2√2 - 7)] / (π - √2) =
= [2π - 2√2] / (π - √2) =
= 2((π - √2)) / (π - √2) =
=2
Felipecps:
obrigado
Perguntas interessantes